A Model Investigation of Aerosol‐Induced Changes in the East Asian Winter Monsoon - Zhen Liu; Yi Ming; Lin Wang; Massimo Bollasina; Ming Luo; Ngar‐Cheung Lau; Steve Hung‐Lam Yim (Geophysical Research Letters)
Abstract The response of the East Asian winter monsoon (EAWM) circulation to aerosols is studied using a coupled atmosphere‐slab ocean general circulation model. In the extratropics, the aerosol‐induced cooling in the midlatitudes leads to an intensified subtropical jet stream, a deepened East Asian trough, and thus an enhanced EAWM. In the tropics, the local Hadley circulation shifts southward to compensate for the interhemispheric asymmetry in aerosol radiative cooling. Anomalous subsidence at around 10°N leads to a salient anticyclone to the southwest of the Philippines. The associated southwesterlies advect abundant moisture to South China, resulting in local precipitation increases and suggesting a weaker EAWM. The EAWM response to aerosol forcing is thus driven by a competition between tropical and extratropical mechanisms, which has important implications for the future monsoon evolution, as aerosol changes may follow different regional‐dependent trajectories.